Stress Management: Preventing Stress Through Lifestyle Management - Suzanna Smith; Joe Pergola (EDIS, 2003)
In today's world, most of us can't avoid stress. We can learn ways to take care of ourselves so stress does not become a problem. Taking care of yourself is the first step in stress management. This fact sheet highlights some basic lifestyle practices that keep you healthy and strong so you can prevent stress. This document is FCS2077B, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida. First Publication: June 1989 as FCS2081. Reviewed: August 1999. Revised: January 2003.